K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

22 tháng 4 2016

đề thiếu

22 tháng 4 2016

đề đúng mà

22 tháng 4 2016

vì a+b+c=0 => a+b= -c; b+c=-a; c+a=-b

(1+a/b)(1+b/c)(1+c/a)

=(a+b/b)(b+c/c)(a+c/a)

= (-c/b)(-a/c)(-b/a)

=-1

22 tháng 4 2016

Thay a = -2 ; b = 1 ; c = 1 ( vì -2 + 1 + 1 = 0 )

Ta có : \(A=\left(1+\frac{-2}{1}\right)\left(1+\frac{1}{1}\right)\left(1+\frac{1}{-2}\right)\)

           \(A=-1.2..\frac{1}{2}\)

           \(A=-1\)

\(1\)